Effect of competition between petroleum-degrading bacteria and indigenous compost microorganisms on the efficiency of petroleum sludge bioremediation: field application of mineral-based culture in the composting process - Abtahi, Hamid; Parhamfar, Milad; Saeedi, Reza; Villaseñor, José; Sartaj, Majid; Kumar, Vinod; Coulon, Frederic; Parhamfar, Maryam; Didehdar, Mojtaba; Seifi, Hamed; Koolivand, Ali (Elsevier, 2020)
The effect of competition between isolated petroleum-degrading bacteria (PDB) and indigenous compost microorganisms (ICM) on the efficiency of composting process in bioremediation of petroleum waste sludge (PWS) was investigated. After isolating two native PDB (Acinetobacter radioresistens strain KA5 and Enterobacter hormaechei strain KA6) from PWS, their ability for growth and crude oil degradation was examined in the mineral-based culture (MBC). Then, the PDB isolate were inoculated into the composting experiments and operated for 12 weeks. The results showed that the PDB degraded 21.65–68.73% of crude oil (1–5%) in the MBC after 7 days. The PDB removed 84.30% of total petroleum hydrocarbon (TPHs) in the composting bioreactor containing the initial TPH level of 20 g kg−1. Removal of petroleum hydrocarbons (PHCs) in the composting experiments proceeded according to the first-order kinetics. The computed values of degradation rate constants and half-lives showed a better performance of the PDB than ICM for TPHs removal. This finding suggests that simultaneous application of the PDB and ICM in the composting reactors resulted in a decline in the effectiveness of the PDB which is due to competition between them. The study also verified that the capability of PDB in degrading PHCs can be successfully scaled-up from MBC to composting process.
Keywords: Petroleum waste sludge; Petroleum-degrading bacteria; Indigenous compost microorganisms; Bioremediation